Legislative Oversight Mechanisms under the DPR Rules of Procedure: Implications for Checks and Balances in Indonesia - Mochamad Haikal Badjeber; Syamsul Hadi (Fakultas Syariah INSURI Ponorogo, 2026)
This study examines how the House of Representatives (DPR) exercises its legislative oversight function through its Rules of Procedure to strengthen the principle of checks and balances within Indonesia's constitutional system. This study employs a normative legal method using a juridical and conceptual approach, supported by relevant legal materials. The findings indicate that the DPR's Rules of Procedure, particularly the provisions on periodic evaluations of state officials appointed through parliamentary mechanisms, strengthen oversight by introducing an evaluation mechanism that produces binding recommendations. This framework enables a more structured assessment of officials' performance and accountability. However, several challenges remain, including the lack of clear, measurable evaluation criteria, the risk of political subjectivity, and limitations in ensuring institutional independence. These issues may undermine the effectiveness and credibility of the oversight process. Therefore, improvements are needed by establishing standardized evaluation parameters, increasing transparency, and strengthening institutional independence to ensure that the DPR's oversight functions operate effectively, objectively, and accountably.